Politik Hukum Pengelolaan Sumber Daya Alam Menurut Pasal 33 UUD 1945 - Rachman, Irfan Nur (Jurnal Konstitusi, 2016)
Indonesia which is located in southeastern asia has a lot of natural resources. This situation has made indonesia was one of the purpose of foreign capital investment especially the mining sector, besides the forestry sector, and water resources management. It was because the lack of our country in managing the source of natural resources, good of the aspect of capital, aspects human resources, and facets technology. As a result of natural resources that we have not can be used to welfare of the people maximally.Ironically, our country having of natural resources, but contributed the most to state budget (APBN) not from the results of the management of natural resources, but of tax sector. Hence in managing natural resources in indonesia need to consider article 33 constitution 1945 containing the political legal in the management of natural resources, so the purpose of natural resources to public welfare can be achieved maximally.